ANALISIS PRODUKSI GARAM DI KABUPATEN PIDIE DAN KABUPATEN PIDIE JAYA - T. Iqbal Safriza N; Cut Zakia Rizki (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study aims to determine the business analysis compare the production of salt farmers in pidie and pidie jaya districts and analyze in pidie district and pidie jaya regency. The analytical method used is descriptive analysis method using primary data, the number of samples used in this method is 30 respondents of salt farmers in the district pidie and 30 respondents in kab. Pidie jaya. Determination of the amount of samples using the large sample n method. The results showed that salt production in pidie district reached 2 tons per month with an average price level of rp. 4,500 per kg, while in pidie jaya regency the production of salt per month reaches 1 ton with an average price of rp. 3,973.33, differences in the level of salt production in pidie and pidie jaya districts are caused by the use of equipment and the capacity of production equipment in each district that farmers use differently besides the capital factor also influences the level of salt production in kab. Pidie jaya.Keywords: Cost Analysis, Marketing Margin, Marketing Channel, Random Purposive Sampling